Une étape primordiale dans l’évaluation d’une politique de développement durable - Karine Bourgeois; Dominique Vollet; Alain Guerard (Développement Durable et Territoires)
An important step in a sustainable policy evaluation: the conception of terms of reference, The experience of the Land Management Contract mid-term review in Limousin. Terms of reference and particularly evaluative questions definition is one of the most important stage in evaluation process. This last aims to analyse the context of the policy and its theory  of action. In order to define, in a pertinent way, priority evaluative questions, both political analysis and implementation analysis (an interdisciplinary method) are required, moreover when the policy is defined in a regional and co-operation framework. In the case of the Land Management Contract (LMC) mid-term review, an objective tree has been drawn up to identify which social and economical mechanisms have been implemented to achieve the main objectives of the Limousin program (hold in place sustainable farms, keep a balanced territorial occupation and maintain a certain environmental quality). A first implementation analysis emphasized some characteristics of LMC in Limousin : low level of LMC regionalisation, lacks in priority objectives targeting…. Four evaluative questions fields have been finally chosen depending on i) the probability of using the results obtained, ii) the possibility of answering the questions and iii) the relevance of the questions allowing for the program objectives. These fields mainly concern i) the level of LMC regionalisation, ii) its  sustainable dimension  and iii) its capacity to increase the local value-added. In the end, terms of reference conception can help rural area management by implying agricultural policy rural partners and, consequently, a better environmental public goods management.